Parametric study of soxhlet extraction of phenolic compounds from vernonia amygdalina leaves - Alara, Oluwaseun Ruth; Abdurahman, Nour Hamid; Abdul Mudalip, Siti Kholijah; Ukaegbu, Chinonso Ishmael; Azhari, Nour Hamid; Kabbashi, Nassereldeen Ahmed (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2018)
—Phenolic compounds are important secondary metabolites with different pharmacological activities. The effects of extraction parameters of Soxhlet extraction method which include extraction time, solid-to-solvent ratio and ethanol concentration on the recoveries of extraction yields, total phenolic content (TPC) and total flavonoid content (TFC) from extracts of Vernonia amygdalina leaves were investigated in this study using one-factor-at-a-time experiment (OFAT). Then,the functional group characterization of the extracts at maximum conditions was carried out. The results obtained showed that the three considered extraction parameters significantly influence the recoveries of extraction yield, TPC and TFC. Highest recoveries of extraction yield (14.22±0.19% w/w), TPC (75.94±2.15 mg GAE/g d.w.) and TFC (46.53±1.14 mg QE/g d.w.) were obtained at extraction time of 2 h, solid-to-solvent ratio of 1:20 g/mL and ethanol concentration of 60% v/v. Moreover, six major peaks were identified from the Soxhlet extraction of V. amygdalina leaves at maximum conditions using Fourier transform infrared spectroscopy (FTIR) analysis. Thus, this study showed that V. amygdalina leaf is a potential source of phenolic compounds which can be influence by the extraction parameters.